An Ecolinguistics Perspectives For English Syllabus Development - Tjendani, Endah Nur; Suastra, I Made; Mbete, Aron Meko; Seri Malini, Ni Luh Nyoman (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-July, 2019)
This current study was intended to develop the ecolinguistic perspective-based syllabus. The descriptive qualitative method was applied and natural phenomena were used to develop syllabus. The phenomena focused on to what extent English was mastered by learners and what learning and teaching strategies were applied. The data were obtained through test, questionnaire and direct observation for the need analysis. The State Document related to the curriculum policy was referred to in the situation analysis. The syllabus was developed based on the results of the need analysis and situation analysis and the ecolinguistic perpective-related theories. The contents of the syllabus were developed based on the following elements; they are text, context, linguistic elements, learning situation, teaching and learning activities ( Kegiatan Belajar Mengajar , abbreviated to KBM) and evaluation. The content of the text was adjusted to the transactional and interpersonal functions. The context was created based on the inter-, intra-, and trans-cultural contexts of the ecological, social and ideological dimensions. KBM was prepared in accordance with the cognitive linguistic process for the language-related activities and based on the situation chosen by learners for the language production. The outcome of language performance was measured using the performance assessment system, causing the contents of the syllabus to reflect that one element was connected with another in such a way that they formed one integral language meaning.